Defined, But Not Confined: Transnationalism, Transcendence, and Exclusion In the Works of Horatio Parker - Willmann, Hannah (Université d'Ottawa / University of Ottawa, 2020)
In this thesis, I demonstrate the relationship of transnationalism, transcendence, and exclusion in the life, works, and words of Horatio Parker (1863-1919). Parker was an organist, composer, and the dean of the School of Music at Yale from 1904 until his death. Although his reputation has since waned, during his lifetime he was a sought-after speaker and composer, gaining recognition across the United States and in England. This thesis engages with three categories of Parker’s repertoire including orchestral, choral/liturgical, and song, and employs intertextuality as the main method of analysis. Parker, like many of his contemporaries, rejected Antonin Dvořák’s 1893 suggestion to American composers that a national idiom could be founded on African American and Native American musics. In combination with his lectures on the topic, I argue that Parker’s symphonic poem A Northern Ballad may be read as his response to Dvořák’s claim. Using many techniques reminiscent of Dvořák’s “New World” Symphony, Parker’s work transcends national boundaries rather than defining or being defined by them. Of greater concern to Parker than the perceived national characteristics of a work was that it should acknowledge music’s spiritual significance. Although the belief in music as a transcendent art frequently divorced music from words and from function, as a devout Christian, Parker sought to reunite the inherently “religious” quality of music with religious service, in works such as Hora Novissima and Light’s Glittering Morn. I frame Parker’s efforts in the context of the writings of John Sullivan Dwight (1813-1893), Wilhelm Wackenroder (1773-1798), and E.T.A. Hoffmann (1776-1822), all major proponents of musical transcendence. In general, appeals to transcendence idolized Beethoven and defined beauty by Eurocentric standards, establishing a false hierarchy that resulted in exclusion. The work of Parker, and other American composers, fuelled also by the false hierarchy of racism, continued to propagate exclusion. The final chapter of this thesis thus contributes to efforts to decolonise Parker’s settler colonial attitudes and examine how these influenced his musical choices.
Keywords: Music; Transcendence; Transnationalism